La gestión administrativa y su incidencia en la atención al usuario en la Agencia nacional de tránsito de los Ríos – sucursal Babahoyo”. - Sandoval Vite, Grace Lorena (2015)
In the Institution there is a suitable model for developing appropriate administrative processes to achieve user satisfaction. Not being defined the activities and responsibilities of the actors in the process and be continuous rotation of personnel managers and employees, the time of engagement and productivity thereof is extended. There is little communication between departments, which causes everyone to work individually and not on processes. The sample must be representative of the population of interest and the information collected is limited to the questions outlined by composing the pre-coded questionnaire designed for this purpose.